Pattern formation in E. coli through negative chemotaxis: Instability, condensation, and merging - Nir Livne; Ady Vaknin; Oded Agam (Physical Review Research)
Motile bacteria can migrate along chemical gradients in a process known as chemotaxis. When exposed to uniform environmental stress, Escherichia coli cells coordinate their chemotactic responses to form millimeter-sized condensates containing hundreds of thousands of motile cells. In this study, we combined experiments with mathematical modeling based on modified Keller-Segel equations to investigate the dynamics of this collective behavior across three distinct timescales: the shortest timescale, where spatial instability emerges; an intermediate timescale, where quasistationary bacterial condensates form; and finally, a longer timescale, during which neighboring bacterial accumulations coalesce. The model closely agrees with experimental results, quantitatively capturing the observed instability, the shape of mature condensates, and their coalescence dynamics. Specifically, we found that the force between neighboring bacterial accumulations decays exponentially with distance due to screening effects. We suggest that the model presented here could describe more broadly the dynamics of stress-induced condensation mediated by bacterial chemotaxis.